(untitled) (Scientific journal of the Fergana State University, 2024)
The advantages of the thermoelectric cooling method (small dimensions and weight of thermoelements, absence of moving parts, relatively short ramp-up time, etc.) make it possible in some cases to give preference to thermoelectric cooling devices over compression and absorption type refrigeration devices.